2021
DOI: 10.3389/fevo.2021.772812
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Dietary Wariness Is Predicted by Head Color in a Specialist Feeder, the Gouldian Finch

Abstract: Shifts in resource availability due to environmental change are increasingly confronting animals with unfamiliar food types. Species that can rapidly accept new food types may be better adapted to ecological change. Intuitively, dietary generalists are expected to accept new food types when resources change, while dietary specialists would be more averse to adopting novel food. However, most studies investigating changes in dietary breadth focus on generalist species and do not delve into potential individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 110 publications
(204 reference statements)
0
4
0
Order By: Relevance
“…While Gouldian Finches do not show a general preference for feature or spatial cues, individual preferences might be affected by the specific characteristics of a bird. Prediction 2a entailed that head colour morphs, which represent resident or nomadic cognitive styles, respectively, affect cue preferences, with black-headed birds potentially going for feature cues and red-headed birds for spatial cues [34,35]. However, no effects of head colour/cognitive style on cue preference were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Gouldian Finches do not show a general preference for feature or spatial cues, individual preferences might be affected by the specific characteristics of a bird. Prediction 2a entailed that head colour morphs, which represent resident or nomadic cognitive styles, respectively, affect cue preferences, with black-headed birds potentially going for feature cues and red-headed birds for spatial cues [34,35]. However, no effects of head colour/cognitive style on cue preference were found.…”
Section: Discussionmentioning
confidence: 99%
“…Red-headed Gouldian Finches are more aggressive but less explorative, while black-headed birds are less aggressive but more explorative [33]. Moreover, a recent study about the cognitive differences between Gouldian Finches suggested that blackheaded birds invest more in local exploration and information gathering, resembling a resident cognitive style, while red-headed birds are better equipped for the exploration of larger areas, resembling a migratory/nomadic cognitive style [34,35]. However, little is known about the influence of the morphs on foraging strategies in Gouldian Finches.…”
Section: Introductionmentioning
confidence: 99%
“…Head colour signals the bird’s personality. Black-headed birds are less aggressive than red-headed birds and explore changes in their familiar environment quickly [ 48 , 49 ], whereas red-headed birds are more likely to venture into new environments and accept new food faster [ 50 , 51 ]. Moreover, black-headed females are bolder at waterholes than all other birds and take the lead when descending to drink [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Red-headed birds are more aggressive [ 47 , 48 , 49 ] but take less risk in potentially dangerous situations and are less explorative of changes in their environment than black-headed birds [ 49 , 50 ]. However, red-headed birds enter unfamiliar environments faster and accept novel food quicker than black-headed birds [ 51 , 52 ]. Earlier experiments on background matching have shown that Gouldian finches prefer a simple green background over a patterned multi-color background [ 33 ].…”
Section: Introductionmentioning
confidence: 99%